2010
DOI: 10.1007/s11307-010-0398-6
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Radiation Dosimetry of the Glycine Transporter-1 Ligand 11C-GSK931145 Determined from Primate and Human Whole-Body PET

Abstract: Human PET imaging of the glycine transporter-1 with (11)C-GSK931145 results in a moderate effective human radiation dose, which allows for multiple PET examinations in the same individual. Among the three methods compared to delineate ROIs, the organ subsampling method shows the best balance between quantitative accuracy and practical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Inter-and intra-operator variability of the different methods to obtain dosimetry estimates was evaluated using clinical data acquired in an earlier study [12]. In such study, eight healthy human volunteers (4 M /4 F) underwent wholebody PET/CT scans on a General Electric Discovery ST scanner which used a 3-dimensional mode protocol.…”
Section: Impact Of Inter-and Intra-operator Variability Of Roi Drawinmentioning
confidence: 99%
See 4 more Smart Citations
“…Inter-and intra-operator variability of the different methods to obtain dosimetry estimates was evaluated using clinical data acquired in an earlier study [12]. In such study, eight healthy human volunteers (4 M /4 F) underwent wholebody PET/CT scans on a General Electric Discovery ST scanner which used a 3-dimensional mode protocol.…”
Section: Impact Of Inter-and Intra-operator Variability Of Roi Drawinmentioning
confidence: 99%
“…For activity quantification in PET planar images and according to previous works, there were no background susbstraction. In such studies it was demonstrated that analysis of compressed planar images were comparable to tomographic images, but with a slight overestimation (conservative calculation) [8][9][11][12].…”
Section: Impact Of Inter-and Intra-operator Variability Of Roi Drawinmentioning
confidence: 99%
See 3 more Smart Citations